The Science of Sound Recording. - Kadis, Jay (Elsevier Science, 2012)
The Science of SoundÈRecordingẅill provideÿou with more than just an introduction to sound and recording, it will allow you to dive rightïnto some of the technical areas thatöftenäppear overwhelming to anyone without an electrical engineering or physics background.È¨The Scienceöf Sound Recordingḧelps you build a basic foundation of scientific principles, explaining how recording really works. Packed with valuable must know information, ïllustrations and examples of 'worked through' equationsẗhis bookïntroduces the.